2020
DOI: 10.1177/0145561320972604
|View full text |Cite
|
Sign up to set email alerts
|

ENT Manifestations of Celiac Disease: A Scholarly Review

Abstract: Objectives: Celiac disease is a common multisystemic autoimmune disorder. It is now increasingly recognized that it may present with extraintestinal manifestations which contribute to the difficulty in its diagnosis. The objective of this scholarly review was to examine the extraintestinal ENT manifestations of celiac disease and its pathophysiology and management, in order to highlight that some patients with celiac disease may present initially to the otolaryngologist. Improving awareness of celiac disease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…[2] In a recent review, ear-nose-throat manifestations of CD were analyzed, and sensorineural hearing loss, obstructive sleep apnea, nasal septal perforation, epistaxis, and vertigo with nystagmus were reported to be associated with immunologically mediated mechanisms. [4] In conclusion, clinicians should be aware that CD may also present with vertigo, and especially in patients with recurrent and prolonged vertigo attacks, CD should also be ruled out.…”
Section: Discussionmentioning
confidence: 95%
“…[2] In a recent review, ear-nose-throat manifestations of CD were analyzed, and sensorineural hearing loss, obstructive sleep apnea, nasal septal perforation, epistaxis, and vertigo with nystagmus were reported to be associated with immunologically mediated mechanisms. [4] In conclusion, clinicians should be aware that CD may also present with vertigo, and especially in patients with recurrent and prolonged vertigo attacks, CD should also be ruled out.…”
Section: Discussionmentioning
confidence: 95%
“…A literature review including 17 studies was conducted by Karunaratne and Karunaratne to identify the relationships between CeD and ear and nose manifestations [ 22 ]. Research targets included sensorineural hearing loss, obstructive sleep apnea, nasal septal perforation, and epistaxis.…”
Section: Oral Cavity Nose and Earsmentioning
confidence: 99%
“…SNHL accounts for approximately 90% of reported hearing loss in the general population, is usually permanent, and can be mild, moderate, severe, profound, or total. The pathological mechanism behind SNHL is not entirely clear and several mechanisms such as malabsorption and immune-mediated neurological damage, comprising autoantibodies, autoreactive T cells, and immune complex deposition, have been proposed [50,51]. Most used methods for the examination of hearing complaints were pure-tone audiometry (PTA), tympanometry, transiently evoked otoacoustic emission (TEOAE), distortion product otoacoustic emission (DPOAE), and contralateral suppression of the TEOAE.…”
Section: Sensorineural Hearing Lossmentioning
confidence: 99%
“…Hemorrhagic events are common as part of the clinical spectrum of adult patients with CeD. In few cases, CeD has been linked to nasal septal perforation and epistaxis [50]. Case reports of 46 Romanian CeD patients with hemorrhagic manifestations, aged between 19 and 74 years, revealed that one patient suffered from bleeding nasal septal perforation and further three cases from life-threatened epistaxis, related to vitamin K and vitamin D malabsorption [59].…”
Section: Nasal Abnormalitiesmentioning
confidence: 99%